ANALISIS KATA AFIKSASI DALAM LIRIK LAGU POP BALI BERJUDUL “SATYA” KARYA DEK ULIK - Ni Putu Gadis Pustika Sari (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2026)
This study aims at describing the use of affixation in the lyrics of the Balinese pop song entitled "Satya" by Dék Ulik. This study uses a qualitative descriptive method. The data used comes from the lyrics of the song "Satya" by Dék Ulik which are available on internet sites and the YouTube platform. The data were collected using the observation method with note-taking techniques and analyzed through identification and classification of affixation forms. The results of the study indicate that there is a lot of use of affixation in the Balinese pop song entitled "Satya" by Dek Ulik. There are 24 words containing affixation in the lyrics of this song. Of the 24 affixed words found, suffixes have the highest percentage of use. There are 13 words consisting of the suffixes -ang, -ing, -an, -né, -n and -é. The most commonly found suffix is the suffix -ang, while the least commonly found suffix is the suffix -ne. The prefixes found are 5 words consisting of Ka-, Ma-, Tu- and I-. The confixes found are 1 word consisting of the confixes Ma-...-an.  Nasalization found in 1 word, namely nasalization Ng-. Nasalization and suffixes found in 3 words, namely nasalization Ng-, N- and suffix -in. Nasalization and confixes found in 1 word, namely with nasalization n- and confix Ma-…-an.